Prospects for nanotechnology in poultry farming - Boltianska, Natalia; Болтянська, Наталя Іванівна; Болтянская, Наталья Ивановна; Boltianskyi, Oleh; Болтянський, Олег Володимирович; Болтянский, Олег Владимирович (Луцький НТУ, 2021)
In organizing the effective marketing of poultry products, their safety and high quality play an important role. The urgency of this problem is due to the increased attention of the population to a healthy lifestyle. Only clean food products of the industry, high quality and environmental friendliness of which are confirmed by international standards, can attract the consumer and provide the enterprise with profit, which has become a prerequisite for successful and effective entrepreneurship. It is high-quality products, especially enriched with nutrients and microelements, that are now becoming the defining criterion for the competitiveness of a poultry enterprise
Keywords: sales of poultry products; environmental friendliness of food products; high quality products; competitiveness poultry farms; ecological poultry farming